2011
DOI: 10.1016/j.jval.2010.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Linezolid, Daptomycin, and Vancomycin in Methicillin-Resistant Staphylococcus aureus: Complicated Skin and Skin Structure Infection Using Bayesian Methods for Evidence Synthesis

Abstract: Linezolid and daptomycin are potentially cost-effective based on the assumptions of the DA model; however, linezolid appears to be more cost-effective compared to daptomycin and vancomycin for MRSA cSSSIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 50 publications
7
22
0
Order By: Relevance
“…Their study found that total direct costs were lower for daptomycin compared to vancomycin, as a result of the reduced length of stay in hospital and the higher success rates with daptomycin. Similar to the analysis presented here, the findings by Bounthavong et al [26 ]were sensitive to the duration of daptomycin treatment. …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Their study found that total direct costs were lower for daptomycin compared to vancomycin, as a result of the reduced length of stay in hospital and the higher success rates with daptomycin. Similar to the analysis presented here, the findings by Bounthavong et al [26 ]were sensitive to the duration of daptomycin treatment. …”
Section: Discussionsupporting
confidence: 90%
“…Bounthavong et al [26 ]used Bayesian methods for evidence synthesis to generate efficacy and safety parameters for a cost-effectiveness analysis model from the perspective of health-care in the USA. Their study found that total direct costs were lower for daptomycin compared to vancomycin, as a result of the reduced length of stay in hospital and the higher success rates with daptomycin.…”
Section: Discussionmentioning
confidence: 99%
“…Bounthavong et al carried out a cost effectiveness analysis of linezolid, daptomycin, and vancomycin in MRSA cSSTIs using a decision analytical model based on efficacy and safety parameters 172. The total direct costs of linezolid, daptomycin, and vancomycin were USD $18,057, $20,698, and $23,671, respectively.…”
Section: Cost Effectivenessmentioning
confidence: 99%
“…36 More recently, a decision analytic model was developed to evaluate the cost-effectiveness of daptomycin, linezolid, and vancomycin in MRSA cSSTIs using Bayesian methods for evidence synthesis. 37 In this study, linezolid was cost-effective compared to vancomycin or daptomycin in the base-case as well as in most of the sensitivity analyses due primarily to decreased length of stay and decreased total direct costs for cSSTIs. 37 Logman, et al performed a network meta-analysis evaluating the pooled microbiological success rates for linezolid, daptomycin, telavancin, tigecycline, dalbavancin, and vancomycin.…”
Section: Current Approved Gram-positive Agentsmentioning
confidence: 77%
“…37 In this study, linezolid was cost-effective compared to vancomycin or daptomycin in the base-case as well as in most of the sensitivity analyses due primarily to decreased length of stay and decreased total direct costs for cSSTIs. 37 Logman, et al performed a network meta-analysis evaluating the pooled microbiological success rates for linezolid, daptomycin, telavancin, tigecycline, dalbavancin, and vancomycin. 38 The results provided a relative difference in microbiological cure rates using Bayesian meta-analysis techniques in the absence of direct head-to-head trials.…”
Section: Current Approved Gram-positive Agentsmentioning
confidence: 77%